Iowa RBA, February 2, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Email for the Iowa RBA for February 2, 1998. Highlights include Prairie Falcon, Glaucous Gull, and Eurasian Collared Dove. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed